Implementación de un software educativo y su influencia en el proceso de enseñanza-aprendizaje en la asignatura de computación de primer año de bachillerato del Instituto Tecnológico Ismael Peréz Pazmiño de la ciudad de Machala período lectivo 2012-2013. - Bravo Muñoz, Mercedes Lucelina (2013)
I investigate this work is an aid for teachers Informatics area can provide much better his chair as educational institutions do not have an updated to the subject Computer software.